(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study investigates the relationship between maternal lipid profile levels at the time of delivery and neonatal birth weight. Maternal lipid metabolism undergoes significant changes during pregnancy, influencing fetal development and birth outcomes. We aim to elucidate the correlation between specific lipid parameters total cholesterol, triglycerides, HDL cholesterol, and LDL cholesterol and neonatal birth weight. By analyzing data from a cohort of pregnant women, we seek to identify lipid profile patterns associated with low and high birth weights, contributing to improved maternal and neonatal healthcare strategies.